Fishing boats in El-Max - Osman, Yomna (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
El-Max is situated within the city of Alexandria, Egypt, a prominent coastal metropolis in northern Egypt. Specifically, it is located adjacent to the Mahmoudiya canal, which serves as a vital waterway connecting the Nile River to the Mediterranean Sea. This strategic location not only facilitates fishing activities but also underscores El-Max’s historical significance as a maritime hub within the larger urban landscape of Alexandria. El-Max region stands as a quintessential example of a geographic area deeply entrenched in maritime traditions, characterized by its rich fishing heritage and boat culture. This academic study explores the fishing heritage of El-Max, and examines the integral role of boats within El-Max’s maritime ecosystem, highlighting their diverse typologies. By scrutinizing the craftsmanship behind boat construction and the socio-cultural rituals associated with boat ownership and usage, this research unveils the profound connections between boats and the identities of El-Max inhabitants. Moreover, this research paper aims to document El-Max region as a local cultural heritage with its distinctive character. It highlights the importance of documenting the region in light of development projects undertaken by the state, which often involve significant alterations to El-Max area. In conclusion, this paper emphasizes the urgency of documenting El-Max as a testament to its unique cultural heritage amid ongoing development pressures, the significance of fishing boats in El-Max extends far beyond their utilitarian function; they are emblematic of a deeply ingrained cultural heritage that binds together generations of coastal communities. As symbols of resilience, craftsmanship, and communal identity, these boats embody the rich maritime traditions of the region.